La metafísica inmortalista - Antelo, Raúl (Universidad Nacional del Litoral, 2020)
I propose to read two texts by Spanish writer Ramón Gómez de la Serna (1988–1963). In the first one, the fetish (Pompei) is a lot more miraculous as only a few of those who believe in it have seen. The other one, on a free aura, shows that life can only be given through the movement of survival as an intertwinement of life and death, i.e., an autoimmunity of mortality.